Theory and Modern Applications

Some identities of Bernoulli, Euler and Abel polynomials arising from umbral calculus

Abstract

In this paper, we derive some identities of Bernoulli, Euler, and Abel polynomials arising from umbral calculus.

MSC:05A10, 05A19.

1 Introduction

Let be the set of all formal power series in the variable t over with

$\mathcal{F}=\left\{f\left(t\right)=\sum _{k=0}^{\mathrm{\infty }}\frac{{a}_{k}}{k!}{t}^{k}|{a}_{k}\in \mathbb{C}\right\}.$
(1.1)

Let us assume that is the algebra of polynomials in the variable x over and ${\mathbb{P}}^{\ast }$ is the vector space of all linear functionals on . $〈L|p\left(x\right)〉$ denotes the action of the linear functional L on a polynomial $p\left(x\right)$, and we remind that the vector space structure on ${\mathbb{P}}^{\ast }$ is defined by

$\begin{array}{c}〈L+M|p\left(x\right)〉=〈L|p\left(x\right)〉+〈M|p\left(x\right)〉,\hfill \\ 〈cL|p\left(x\right)〉=c〈L|p\left(x\right)〉,\hfill \end{array}$

where c is a complex constant (see [14]).

The formal power series

$f\left(t\right)=\sum _{k=0}^{\mathrm{\infty }}\frac{{a}_{k}}{k!}{t}^{k}\in \mathcal{F}$
(1.2)

defines a linear functional on by setting

(1.3)

Thus, by (1.2) and (1.3), we get

$〈{t}^{k}|{x}^{n}〉=n!{\delta }_{n,k}\phantom{\rule{1em}{0ex}}\left(n,k\ge 0\right),$
(1.4)

where ${\delta }_{n,k}$ is the Kronecker symbol (see [3]).

For ${f}_{L}\left(t\right)={\sum }_{k=0}^{\mathrm{\infty }}\frac{〈L|{x}^{k}〉}{k!}{t}^{k}$, from (1.4), we have

$〈{f}_{L}\left(t\right)|{x}^{n}〉=〈L|{x}^{n}〉,\phantom{\rule{1em}{0ex}}n\ge 0.$
(1.5)

By (1.5), we get $L={f}_{L}\left(t\right)$. The map $L↦{f}_{L}\left(t\right)$ is a vector space isomorphism from ${\mathbb{P}}^{\ast }$ onto . So, denotes both the algebra of formal power series in t and the vector space of all linear functionals on , and so an element $f\left(t\right)$ of is thought of as both a formal power series and a linear functional (see [13]). We call the umbral algebra, and the study of umbral algebra is called umbral calculus (see [13]).

The order $o\left(f\left(t\right)\right)$ of the nonzero power series $f\left(t\right)$ is the smallest integer k for which the coefficient of ${t}^{k}$ does not vanish. If $o\left(f\left(t\right)\right)=1$, then $f\left(t\right)$ is called a delta series. If $o\left(f\left(t\right)\right)=0$, then $f\left(t\right)$ is called an invertible series (see [3]).

Let ${S}_{n}\left(x\right)$ be polynomials in the variable x with degree n, and let $o\left(f\left(t\right)\right)=1$ and $o\left(g\left(t\right)\right)=0$. Then there exists a unique sequence ${S}_{n}\left(x\right)$ such that $〈g\left(t\right)f{\left(t\right)}^{k}|{S}_{n}\left(x\right)〉=n!{\delta }_{n,k}$, where $n,k\ge 0$. The sequence ${S}_{n}\left(x\right)$ is called the Sheffer sequence for $\left(g\left(t\right),f\left(t\right)\right)$, which is denoted by ${S}_{n}\left(x\right)\sim \left(g\left(t\right),f\left(t\right)\right)$ (see [3]).

For $f\left(t\right),g\left(t\right)\in \mathcal{F}$, we have

$f\left(t\right)=\sum _{k=0}^{\mathrm{\infty }}\frac{〈f\left(t\right)|{x}^{k}〉}{k!}{t}^{k},\phantom{\rule{2em}{0ex}}p\left(x\right)=\sum _{k=0}^{\mathrm{\infty }}\frac{〈{t}^{k}|p\left(x\right)〉}{k!}{x}^{k},$
(1.6)

and

$〈f\left(t\right)g\left(t\right)|p\left(x\right)〉=〈f\left(t\right)|g\left(t\right)p\left(x\right)〉=〈g\left(t\right)|f\left(t\right)p\left(x\right)〉\phantom{\rule{1em}{0ex}}\text{(see [3])}.$
(1.7)

By (1.6), we get

$\frac{{d}^{k}p\left(x\right)}{d{x}^{k}}{|}_{x=0}={p}^{\left(k\right)}\left(0\right)=〈{t}^{k}|p\left(x\right)〉\phantom{\rule{1em}{0ex}}\text{and}\phantom{\rule{1em}{0ex}}〈1|{p}^{\left(k\right)}\left(x\right)〉={p}^{\left(k\right)}\left(0\right).$
(1.8)

Thus, from (1.8), we have

${t}^{k}p\left(x\right)={p}^{\left(k\right)}\left(x\right)=\frac{{d}^{k}p\left(x\right)}{d{x}^{k}}\phantom{\rule{1em}{0ex}}\text{(see [1–3])}.$
(1.9)

For ${S}_{n}\left(x\right)\sim \left(g\left(t\right),f\left(t\right)\right)$, the following equations from (1.10) to (1.14) are well known in [3]:

(1.10)
(1.11)
(1.12)
(1.13)

where $\overline{f}\left(t\right)$ is the compositional inverse of $f\left(t\right)$, and

${S}_{n}\left(x+y\right)=\sum _{k=0}^{n}\left(\genfrac{}{}{0}{}{n}{k}\right){p}_{k}\left(y\right){S}_{n-k}\left(x\right)=\sum _{k=0}^{n}\left(\genfrac{}{}{0}{}{n}{k}\right){p}_{k}\left(x\right){S}_{n-k}\left(y\right),$
(1.14)

where ${p}_{k}\left(y\right)=g\left(t\right){S}_{k}\left(y\right)\sim \left(1,f\left(t\right)\right)$.

The Euler polynomials of order r are defined by the generating function to be

${\left(\frac{2}{{e}^{t}+1}\right)}^{r}{e}^{xt}={e}^{{E}^{\left(r\right)}\left(x\right)t}=\sum _{n=0}^{\mathrm{\infty }}\frac{{E}_{n}^{\left(r\right)}\left(x\right)}{n!}{t}^{n}\phantom{\rule{1em}{0ex}}\text{(see [1–3, 5–16])}$
(1.15)

with the usual convention about replacing ${\left({E}^{\left(r\right)}\left(x\right)\right)}^{n}$ by ${E}_{n}^{\left(r\right)}\left(x\right)$. In the special case, $x=0$, ${E}_{n}^{\left(r\right)}\left(0\right)={E}_{n}^{\left(r\right)}$ are called the Euler numbers of order r.

As is well known, the higher-order Bernoulli polynomials are also defined by the generating function to be

${\left(\frac{t}{{e}^{t}-1}\right)}^{r}{e}^{xt}={e}^{{B}^{\left(r\right)}\left(x\right)t}=\sum _{n=0}^{\mathrm{\infty }}\frac{{B}_{n}^{\left(r\right)}\left(x\right)}{n!}{t}^{n}\phantom{\rule{1em}{0ex}}\text{(see [1–3, 5–16])}$
(1.16)

with the usual convention about replacing ${\left({B}^{\left(r\right)}\left(x\right)\right)}^{n}$ by ${B}_{n}^{\left(r\right)}\left(x\right)$. In the special case, $x=0$, ${B}_{n}^{\left(r\right)}\left(0\right)={B}_{n}^{\left(r\right)}$ are called the Bernoulli numbers of order r.

Recently, several researchers have studied the umbral calculus related to special polynomials. In this paper, we derive some interesting identities related to Bernoulli, Euler, and Abel polynomials arising from umbral calculus.

2 Some identities of special polynomials

It is known [3] that

$x{B}_{n-1}^{\left(na\right)}\left(x\right)\sim \left(1,{\left(\frac{{e}^{t}-1}{t}\right)}^{a}t\right),\phantom{\rule{1em}{0ex}}{x}^{n}\sim \left(1,t\right),$
(2.1)

where $n\in \mathbb{N}$ and $a\ne 0$. From (2.1), we have

$\begin{array}{rcl}{x}^{n}& =& x{\left(\frac{{e}^{t}-1}{t}\right)}^{an}{x}^{-1}x{B}_{n-1}^{\left(na\right)}\left(x\right)=x{\left(\frac{{e}^{t}-1}{t}\right)}^{an}{B}_{n-1}^{\left(na\right)}\left(x\right)\\ =& x\sum _{l=0}^{\mathrm{\infty }}\frac{\left(an\right)!}{\left(l+an\right)!}{S}_{2}\left(l+an,an\right){t}^{l}{B}_{n-1}^{\left(na\right)}\left(x\right)\\ =& x\sum _{l=0}^{n-1}\frac{\left(an\right)!}{\left(l+an\right)!}{S}_{2}\left(l+an,an\right){\left(n-1\right)}_{l}{B}_{n-1-l}^{\left(na\right)}\left(x\right),\end{array}$
(2.2)

where ${S}_{2}\left(n,l\right)$ is the Stirling number of the second kind. Therefore, by (2.2), we obtain the following theorem.

Theorem 2.1 For $n\in \mathbb{N}$ and $a\ne 0$, we have

${x}^{n-1}=\sum _{l=0}^{n-1}\frac{\left(an\right)!}{\left(l+an\right)!}{S}_{2}\left(l+an,an\right){\left(n-1\right)}_{l}{B}_{n-1-l}^{\left(na\right)}\left(x\right),$

where ${\left(a\right)}_{n}=a\left(a-1\right)\cdots \left(a-n+1\right)$.

In [3], we note that

${S}_{n}\left(x\right)=\sum _{k=1}^{n}\left(\genfrac{}{}{0}{}{-an}{n-k}\right){\left(n-1\right)}_{n-k}{x}^{k}\sim \left(1,t{\left(1+t\right)}^{a}\right),$
(2.3)

and

${\varphi }_{n}\left(x\right)=\sum _{k=0}^{n}{S}_{2}\left(n,k\right){x}^{k}\sim \left(1,log\left(1+t\right)\right),$
(2.4)

where $a\ne 0$.

For $n\ge 1$, we have

$\begin{array}{rcl}{\varphi }_{n}\left(x\right)& =& x{\left(\frac{t{\left(1+t\right)}^{a}}{log\left(1+t\right)}\right)}^{n}{x}^{-1}{S}_{n}\left(x\right)\\ =& x{\left(\frac{t{\left(1+t\right)}^{a}}{log\left(1+t\right)}\right)}^{n}\sum _{l=1}^{n}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}{x}^{l-1}.\end{array}$
(2.5)

The Bernoulli polynomials ${b}_{n}\left(x\right)$ of the second kind are defined by the generating function to be

$\frac{t}{log\left(1+t\right)}{\left(1+t\right)}^{x}=\sum _{k=0}^{\mathrm{\infty }}{b}_{k}\left(x\right)\frac{{t}^{k}}{k!}\phantom{\rule{1em}{0ex}}\text{(see [3])}.$
(2.6)

By (2.5) and (2.6), we get

$\begin{array}{rcl}{\varphi }_{n}\left(x\right)& =& \sum _{l=1}^{n}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}x{\left(\frac{t{\left(1+t\right)}^{a}}{log\left(1+t\right)}\right)}^{n}{x}^{l-1}\\ =& \sum _{l=1}^{n}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}x{\left(\sum _{k=0}^{\mathrm{\infty }}\frac{{b}_{k}\left(a\right)}{k!}{t}^{k}\right)}^{n}{x}^{l-1}\\ =& \sum _{l=1}^{\mathrm{\infty }}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}x\sum _{k=0}^{\mathrm{\infty }}\left(\sum _{{l}_{1}+\cdots +{l}_{n}=k}\left(\genfrac{}{}{0}{}{k}{{l}_{1},\dots ,{l}_{n}}\right){b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right)\right)\frac{{t}^{k}}{k!}{x}^{l-1}\\ =& \sum _{l=1}^{n}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}x\sum _{k=0}^{l-1}\left(\sum _{{l}_{1}+\cdots +{l}_{n}=k}\left(\genfrac{}{}{0}{}{k}{{l}_{1},\dots ,{l}_{n}}\right){b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right)\right)\frac{{\left(l-1\right)}_{k}}{k!}{x}^{l-1-k}\\ =& \sum _{l=1}^{n}\sum _{k=0}^{l-1}\sum _{{l}_{1}+\cdots +{l}_{n}=k}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}\left(\genfrac{}{}{0}{}{l-1}{k}\right)\left(\genfrac{}{}{0}{}{k}{{l}_{1},\dots ,{l}_{n}}\right){b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right){x}^{l-k}\\ =& \sum _{l=1}^{n}\sum _{m=1}^{l}\sum _{{l}_{1}+\cdots +{l}_{n}=l-m}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}\left(\genfrac{}{}{0}{}{l-1}{m-1}\right)\left(\genfrac{}{}{0}{}{l-m}{{l}_{1},\dots ,{l}_{n}}\right){b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right){x}^{m}\\ =& \sum _{m=1}^{n}\left\{\sum _{l=m}^{n}\sum _{{l}_{1}+\cdots +{l}_{n}=l-m}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}\left(\genfrac{}{}{0}{}{l-1}{m-1}\right)\left(\genfrac{}{}{0}{}{l-m}{{l}_{1},\dots ,{l}_{n}}\right)\\ ×{b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right)\right\}{x}^{m}.\end{array}$
(2.7)

Therefore, by (2.4) and (2.7), we obtain the following theorem.

Theorem 2.2 For $a\ne 0$, $n\ge 1$ with $1\le m\le n$, we have

${S}_{2}\left(n,m\right)=\sum _{l=m}^{n}\sum _{{l}_{1}+\cdots +{l}_{n}=l-m}\left(\genfrac{}{}{0}{}{-an}{n-l}\right){\left(n-1\right)}_{n-l}\left(\genfrac{}{}{0}{}{l-1}{m-1}\right)\left(\genfrac{}{}{0}{}{l-m}{{l}_{1},\dots ,{l}_{n}}\right){b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right).$

It is well known (see [3]) that

${\left(\frac{t}{log\left(1+t\right)}\right)}^{n}{\left(1+t\right)}^{x-1}=\sum _{k=0}^{\mathrm{\infty }}{B}_{k}^{\left(k-n+1\right)}\left(x\right)\frac{{t}^{k}}{k!}.$
(2.8)

Thus, by (2.8), we get

${\left(\frac{t{\left(1+t\right)}^{a}}{log\left(1+t\right)}\right)}^{n}=\sum _{k=0}^{\mathrm{\infty }}{B}_{k}^{\left(k-n+1\right)}\left(an+1\right)\frac{{t}^{k}}{k!},$
(2.9)

and

${\left(\frac{t{\left(1+t\right)}^{a}}{log\left(1+t\right)}\right)}^{n}=\sum _{k=0}^{\mathrm{\infty }}\left(\sum _{{l}_{1}+\cdots +{l}_{n}=k}\left(\genfrac{}{}{0}{}{k}{{l}_{1},\dots ,{l}_{n}}\right){b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right)\right)\frac{{t}^{k}}{k!}.$
(2.10)

Therefore, by (2.9) and (2.10), we obtain the following lemma.

Lemma 2.3 For $n,k\in {\mathbb{Z}}_{+}$, we have

$\sum _{{l}_{1}+\cdots +{l}_{n}=k}\left(\genfrac{}{}{0}{}{k}{{l}_{1},\dots ,{l}_{n}}\right){b}_{{l}_{1}}\left(a\right)\cdots {b}_{{l}_{n}}\left(a\right)={B}_{k}^{\left(k-n+1\right)}\left(an+1\right).$

Let us consider the following sequences:

$\begin{array}{r}{S}_{n}\left(x\right)\sim \left(1,{\left(\frac{{e}^{t}+1}{2}\right)}^{a}t\right)\phantom{\rule{1em}{0ex}}\left(a\in \mathbb{R}\right),\\ {x}^{n}\sim \left(1,t\right)\phantom{\rule{1em}{0ex}}\left(n\ge 0\right).\end{array}$
(2.11)

Then from (2.11), we have

$\begin{array}{rcl}{S}_{n}\left(x\right)& =& x{\left(\frac{2}{{e}^{t}+1}\right)}^{an}{x}^{-1}{x}^{n}=x{\left(\frac{2}{{e}^{t}+1}\right)}^{an}{x}^{n-1}\\ =& x{E}_{n-1}^{\left(an\right)}\left(x\right).\end{array}$
(2.12)

Therefore, by (2.12), we obtain the following proposition.

Proposition 2.4 For $a\in \mathbb{R}$, $n\in \mathbb{N}$, we have

$x{E}_{n-1}^{\left(an\right)}\left(x\right)\sim \left(1,{\left(\frac{{e}^{t}+1}{2}\right)}^{a}t\right).$

The Abel sequence is given by

${A}_{n}\left(x;b\right)=x{\left(x-bn\right)}^{n-1}\sim \left(1,t{e}^{bt}\right)\phantom{\rule{1em}{0ex}}\left(b\ne 0\right).$
(2.13)

By Proposition 2.4 and (2.13), we get

$\begin{array}{rcl}x{E}_{n-1}^{\left(na\right)}\left(x\right)& =& x{\left(\frac{t{e}^{bt}}{{\left(\frac{{e}^{t}+1}{2}\right)}^{a}t}\right)}^{n}{x}^{-1}{A}_{n}\left(x;b\right)\\ =& x{\left(\frac{2}{{e}^{t}+1}\right)}^{an}{e}^{bnt}{x}^{-1}{A}_{n}\left(x;b\right)\\ =& x\left(\sum _{k=0}^{\mathrm{\infty }}\frac{{E}^{\left(an\right)}\left(bn\right)}{k!}{t}^{k}\right){\left(x-bn\right)}^{n-1}\\ =& x\sum _{k=0}^{n-1}\left(\genfrac{}{}{0}{}{n-1}{k}\right){E}_{k}^{\left(an\right)}\left(bn\right){\left(x-bn\right)}^{n-1-k}.\end{array}$
(2.14)

Therefore, by (2.14), we obtain the following theorem.

Theorem 2.5 For $n\in \mathbb{N}$ and $a\in \mathbb{R}$, we have

$\begin{array}{rcl}{E}_{n-1}^{\left(an\right)}\left(x\right)& =& \sum _{k=0}^{n-1}\left(\genfrac{}{}{0}{}{n-1}{k}\right){E}_{k}^{\left(an\right)}\left(bn\right){\left(x-bn\right)}^{n-1-k}\\ =& \sum _{k=0}^{n-1}\left(\genfrac{}{}{0}{}{n-1}{k}\right){E}_{n-1-k}^{\left(an\right)}\left(bn\right){\left(x-bn\right)}^{k}.\end{array}$

Let us consider the following Sheffer sequences:

$\begin{array}{r}{G}_{n}\left(x;a,b\right)\sim \left(1,{e}^{at}\left({e}^{bt}-1\right)\right)\phantom{\rule{1em}{0ex}}\left(b\ne 0\right),\\ {A}_{n}\left(x;c+a\right)\sim \left(1,t{e}^{\left(c+a\right)t}\right)\phantom{\rule{1em}{0ex}}\left(c+a\ne 0\right).\end{array}$
(2.15)

By (2.15), we note that

${G}_{n}\left(x;a,b\right)=\frac{x}{b}{\left(\frac{x-an}{b}-1\right)}_{n-1}.$
(2.16)

For $n\ge 1$, from (2.15), we have

$\begin{array}{rcl}{A}_{n}\left(x;c+a\right)& =& x{\left(\frac{{e}^{at}\left({e}^{bt}-1\right)}{t{e}^{\left(c+a\right)t}}\right)}^{n}{x}^{-1}{G}_{n}\left(x;a,b\right)\\ =& x{\left(\frac{{e}^{bt}-1}{t{e}^{ct}}\right)}^{n}{x}^{-1}{G}_{n}\left(x;a,b\right),\end{array}$
(2.17)

and

$\begin{array}{rcl}\frac{{\left({e}^{t}-1\right)}^{n}}{{e}^{tx}{t}^{n}}& =& \frac{1}{{t}^{n}}\left(n!\sum _{j=n}^{\mathrm{\infty }}{S}_{2}\left(j,n\right)\frac{{t}^{j}}{j!}\right)\left(\sum _{l=0}^{\mathrm{\infty }}\frac{{\left(-1\right)}^{l}}{l!}{x}^{l}{t}^{l}\right)\\ =& \left(n!\sum _{j=0}^{\mathrm{\infty }}{S}_{2}\left(j+n,n\right)\frac{{t}^{j}}{\left(j+n\right)!}\right)\left(\sum _{l=0}^{\mathrm{\infty }}\frac{{\left(-1\right)}^{l}{x}^{l}}{l!}{t}^{l}\right)\\ =& \sum _{k=0}^{\mathrm{\infty }}\left(\sum _{j=0}^{k}{S}_{2}\left(j+n,n\right)\frac{{\left(-1\right)}^{k-j}\left(\genfrac{}{}{0}{}{k}{j}\right)}{\left(\genfrac{}{}{0}{}{j+n}{j}\right)}{x}^{k-j}\right)\frac{{t}^{k}}{k!}.\end{array}$
(2.18)

From (2.18), we can derive the following equation (2.19):

$\frac{{\left({e}^{bt}-1\right)}^{n}}{{e}^{bt\left(\frac{c}{b}n\right)}{\left(bt\right)}^{n}}=\sum _{k=0}^{\mathrm{\infty }}\left(\sum _{j=0}^{k}{\left(-1\right)}^{k-j}\frac{\left(\genfrac{}{}{0}{}{k}{j}\right){S}_{2}\left(j+n,n\right)}{\left(\genfrac{}{}{0}{}{j+n}{j}\right)}{\left(\frac{c}{b}n\right)}^{k-j}\right)\frac{{\left(bt\right)}^{k}}{k!}.$
(2.19)

Thus, by (2.19), we get

${\left(\frac{{e}^{bt}-1}{t{e}^{ct}}\right)}^{n}={b}^{n}\sum _{k=0}^{\mathrm{\infty }}\left(\sum _{j=0}^{k}{\left(-cn\right)}^{k-j}\frac{\left(\genfrac{}{}{0}{}{k}{j}\right){S}_{2}\left(j+n,n\right)}{\left(\genfrac{}{}{0}{}{j+n}{j}\right)}{b}^{j}\right)\frac{{t}^{k}}{k!}.$
(2.20)

From (2.16), (2.17), and (2.20), we can derive the following equation (2.21):

(2.21)

and

${\left(\frac{x-an}{b}-1\right)}_{n-1}=\sum _{l=0}^{n-1}{S}_{1}\left(n-1,l\right){\left(\frac{x-an}{b}-1\right)}^{l},$
(2.22)

where ${S}_{1}\left(n,l\right)$ is the Stirling number of the first kind. By (2.22), we get

$\frac{{t}^{k}}{k!}{\left(\frac{x-an}{b}-1\right)}_{n-1}=\sum _{l=k}^{n-1}{S}_{1}\left(n-1,l\right)\left(\genfrac{}{}{0}{}{l}{k}\right){\left(\frac{x-an}{b}-1\right)}^{l-k}{b}^{-k}.$
(2.23)

Thus, by (2.21) and (2.23), we get

(2.24)

From (1.14), we have

${A}_{n}\left(x;c+a\right)=x{\left(x-\left(c+a\right)n\right)}^{n-1}.$
(2.25)

Therefore, by (2.24) and (2.25), we obtain the following theorem.

Theorem 2.6 For $n\ge 1$, $b\ne 0$, $c+a\ne 0$, we have

$\begin{array}{c}{\left(x-\left(c+a\right)n\right)}^{n-1}\hfill \\ \phantom{\rule{1em}{0ex}}={b}^{n-1}\sum _{k=0}^{n-1}\sum _{j=0}^{k}\sum _{l=k}^{n-1}{\left(-\frac{cn}{b}\right)}^{k-j}\frac{\left(\genfrac{}{}{0}{}{k}{j}\right)\left(\genfrac{}{}{0}{}{l}{k}\right){S}_{2}\left(j+n,n\right){S}_{1}\left(n-1,l\right)}{\left(\genfrac{}{}{0}{}{j+n}{j}\right)}{\left(\frac{x-an}{b}-1\right)}^{l-k}.\hfill \end{array}$

References

1. Dere R, Simsek Y: Applications of umbral algebra to some special polynomials. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2012, 22: 433–438.

2. Kim DS, Kim T: Some identities of Frobenius-Euler polynomials arising from umbral calculus. Adv. Differ. Equ. 2012., 2012: Article ID 196. doi:10.1186/1687–1847–2012–196

3. Roman S: The Umbral Calculus. Dover, New York; 2005.

4. Dere R, Simsek Y: Genocchi polynomials associated with the Umbral algebra. Appl. Math. Comput. 2011, 218: 756–761. 10.1016/j.amc.2011.01.078

5. Araci S, Aslan N, Seo J: A note on the weighted twisted Dirichlet’s type q -Euler numbers and polynomials. Honam Math. J. 2011, 33(3):311–320. 10.5831/HMJ.2011.33.3.311

6. Acikgoz M, Erdal D, Araci S: A new approach to q -Bernoulli numbers and q -Bernoulli polynomials related to q -Bernstein polynomials. Adv. Differ. Equ. 2010., 2010: Article ID 951764

7. Bayad A: Modular properties of elliptic Bernoulli and Euler functions. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2010, 20(3):389–401.

8. Can M, Cenkci M, Kurt V, Simsek Y: Twisted Dedekind type sums associated with Barnes’ type multiple Frobenius-Eulerl-functions. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2009, 18(2):135–160.

9. Carlitz L: The product of two Eulerian polynomials. Math. Mag. 1963, 368: 37–41.

10. Ding D, Yang J: Some identities related to the Apostol-Euler and Apostol-Bernoulli polynomials. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2010, 20(1):7–21.

11. Kim T: New approach to q -Euler, Genocchi numbers and their interpolation functions. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2009, 18(2):105–112.

12. Ozden H, Cangul IN, Simsek Y: Remarks on q -Bernoulli numbers associated with Daehee numbers. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2009, 18(1):41–48.

13. Rim S-H, Joung J, Jin J-H, Lee S-J: A note on the weighted Carlitz’s type q -Euler numbers and q -Bernstein polynomials. Proc. Jangjeon Math. Soc. 2012, 15: 195–201.

14. Ryoo C: Some relations between twisted q -Euler numbers and Bernstein polynomials. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2011, 21(2):217–223.

15. Simsek Y: Special functions related to Dedekind-type DC-sums and their applications. Russ. J. Math. Phys. 2010, 17: 495–508. 10.1134/S1061920810040114

16. Simsek Y: Generating functions of the twisted Bernoulli numbers and polynomials associated with their interpolation functions. Adv. Stud. Contemp. Math - Jang’jun Math. Soc. 2008, 16(2):251–278.

Acknowledgements

The authors express their sincere gratitude to the referees for their valuable suggestions and comments. This paper is supported in part by the Research Grant of Kwangwoon University in 2013.

Author information

Authors

Corresponding author

Correspondence to Taekyun Kim.

Competing interests

The authors declare that they have no competing interests.

Authors’ contributions

All authors contributed equally to the manuscript and typed, read, and approved the final manuscript.

Rights and permissions

Reprints and Permissions

Kim, D.S., Kim, T., Lee, SH. et al. Some identities of Bernoulli, Euler and Abel polynomials arising from umbral calculus. Adv Differ Equ 2013, 15 (2013). https://doi.org/10.1186/1687-1847-2013-15